Real-world effectiveness of amlodipine/valsartan and amlodipine/valsartan/hydrochlorothiazide in high-risk patients and other subgroups - Assaad-Khalil, Samir Helmy (Vasc Health Risk Manag, 2015)
BACKGROUND: The clinical EXCITE (EXperienCe of amlodIpine and valsarTan in hypErtension) study reported clinically relevant blood pressure (BP) reductions across all doses of amlodipine/valsartan (Aml/Val) and Aml/Val/hydrochlorothiazide (HCT) single-pill combinations. The study prospectively observed a multiethnic population of hypertensive patients for 26 weeks who were treated according to routine clinical practice. Here, we present the results in high-risk subgroups including the elderly, obese patients, and patients with diabetes or isolated systolic hypertension. In addition, we present a post hoc analysis as per prior antihypertensive monotherapy and dual therapy. METHODS: Patients prescribed Aml/Val or Aml/Val/HCT were assessed in this 26±8 week, noninterventional, multicenter study across 13 countries in the Middle East and Asia. Changes in mean sitting systolic BP, mean sitting diastolic BP, and overall safety were assessed. RESULTS: Of a total of 9,794 patients analyzed, 8,603 and 1,191 patients were prescribed Aml/Val and Aml/Val/HCT, respectively. Among these, 15.5% were elderly, 32.5% were obese, 31.3% had diabetes, and 9.8% had isolated systolic hypertension. Both Aml/Val and Aml/Val/HCT single-pill combinations, respectively, were associated with clinically relevant and significant mean sitting systolic/diastolic BP reductions across all subgroups: elderly patients (−32.2/−14.3 mmHg and −38.5/−16.5 mmHg), obese patients (−32.2/−17.9 mmHg and −38.5/−18.4 mmHg), diabetic patients (−30.3/−16.1 mmHg and −34.4/−16.6 mmHg), and patients with isolated systolic hypertension (−25.5/−4.1 mmHg and −30.2/−5.9 mmHg). Incremental BP reductions with Aml/Val or Aml/Val/HCT single-pill combinations were also observed in patients receiving prior monotherapy or dual therapy for hypertension. Overall, both Aml/Val and Aml/Val/HCT were generally well tolerated. CONCLUSION: This large, multiethnic study supports the evidence that Aml/Val and Aml/Val/ HCT single-pill combinations are effective in diverse and clinically important subgroups of patients with hypertension.